2001
DOI: 10.1074/jbc.m100907200
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of 55Fe-Labeled Precursors of the Iron-Molybdenum Cofactor of Nitrogenase on NifH and NifX ofAzotobacter vinelandii

Abstract: Iron

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 39 publications
4
33
0
Order By: Relevance
“…First, the ␥ protein binds FeMo-co (13). Second, NifX and VnfX from A. vinelandii are also able to bind FeMo-co (37), 2 as well as NifB-co (32,37). Third, VnfX is also able to bind a FeV-co precursor (vanadiumcontaining iron-sulfur cluster) lacking homocitrate (32).…”
Section: Resultsmentioning
confidence: 99%
“…First, the ␥ protein binds FeMo-co (13). Second, NifX and VnfX from A. vinelandii are also able to bind FeMo-co (37), 2 as well as NifB-co (32,37). Third, VnfX is also able to bind a FeV-co precursor (vanadiumcontaining iron-sulfur cluster) lacking homocitrate (32).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the C-terminal NifX-like domain could indicate that this region in NifB is either involved in binding NifB-co precursors and forming the NifB-co or binding a preformed NifB-co for transfer to another protein in the FeMoco biosynthetic pathway [44] . Although it was evident from previous reports that NifX is capable of binding to NifB-co in one of the stages during FeMoco biosynthesis [30] , a direct proteinprotein interaction between the NifB and NifX proteins had not been demonstrated before. Our results support the idea that there is an interaction between NifB and NifX as found by measuring the β-galactosidase activity of E. coli cotransformants harboring the plasmids pMH6002 (λCI:NifB) and pMH5002 (RNAP:NifX).…”
Section: Interactionmentioning
confidence: 82%
“…Following this, the core is transferred from NifB to the NifEN complex. Based on previous studies and the detection of an interaction between NifB and NifX in our study, it could be possible that NifX facilitates the transfer of the core from NifB to NifEN [30] . It is possible that the addition of homocitrate takes place at this step, since one previous study has shown that the NifX may be involved in specifying the organic acid moiety of the FeMoco precursor [31] .…”
Section: Interaction Of Nifdk (Fusion) and Nifk With Nifxmentioning
confidence: 99%
See 2 more Smart Citations